Health outcomes and health-seeking behaviour following traumatic brain injury among older people: a prospective cohort study in Bangladesh - Rahman, Farah Naz; Das, Sukriti; Chowdhury, Mohammad Rocky Khan; Kader, Manzur; Mashreky, Saidur Rahman (Frontiers in Aging, 2025)
BackgroundOlder adults are at high risk for traumatic brain injury (TBI), yet there is limited evidence on their vulnerability to mortality, morbidity, and associated risk factors in low-and-middle-income countries. This study assessed the burden, health outcomes, and health-seeking behavior of TBI in older adults at the largest teaching hospital in Bangladesh.MethodsThe study analyzed data from individuals aged 60+ years who were part of a prospective observational cohort of TBI patients admitted to a teaching hospital in Dhaka, Bangladesh, from May to June 2017. Data were collected at admission and during discharge or a 30-day follow-up (whichever came earlier) using a pre-tested semi-structured questionnaire, including the Glasgow Coma Scale (GCS), Glasgow Outcome Scale (GOS), and EuroQol-5D-3L. Descriptive analyses assessed the burden, characteristics, and health-seeking behavior for TBI, while relative risks were calculated to evaluate the risk of mortality by socio-demographic characteristics and clinical status.ResultsDuring the study period, 117 older TBI patients were admitted, with 78.6% being male. Road traffic injuries (RTI) accounted for 71.3% of cases, followed by falls (16%). Half of the patients did not receive treatment at the primary and secondary facilities they initially visited, and 16% experienced over 24 h’ delay in treatment initiation. On admission, 25% presented with severe injury (GCS ≤8), and all had a history of loss of consciousness. The mortality rate was 5.2 per 1,000 person-days. Severe mobility issues and anxiety/depression were reported by 11% during follow-up. Bivariate analysis indicated higher mortality risk in patients with low socio-economic status, GCS ≤8, and over 1-h duration of both loss of consciousness and post-traumatic amnesia.ConclusionRTI and falls are major causes of TBI, disproportionately affecting older adults of lower socio-economic status. Treatment accessibility gaps exist, and clinical status at admission is critical for predicting mortality. Findings can inform policies for preventive and rehabilitative strategies, including priority management protocols for older TBI patients in Bangladesh.